BUILDING CHARACTER EDUCATION PERSPECTIVE OF MORAL EDUCATION IN MADRASAH IBTIDAIYAH (Indonesian Journal of Education (INJOE), 2025)
This literature review explains how to build character education from a moral education perspective in madrasah ibtidaiyah. Character education is one of the fundamental efforts in creating learning situations that meet students' self-development needs in learning interactions designed to form students with character. Meanwhile, moral education is very important in forming morals in students. With moral education in the form of activities that have the value of worship implemented in schools, students are accustomed to carrying out good deeds towards God and fellow humans. Character development is an important part of the Islamic education approach. Character education must combine all aspects of cognitive, affective and psychomotor student development into one complete and inseparable unit when applied in madrsah ibtidaiyah. It will be difficult to practice character education if one of these three development aspects is missing. The aim is to shape a person's personality so that it shows superior qualities such as honesty, kindness, responsibility, respect for others, fairness, non- discrimination, hard work, and so on